2003
DOI: 10.1038/sj.jhh.1001601
|View full text |Cite
|
Sign up to set email alerts
|

Relation between the angiotensin-converting enzyme insertion/deletion polymorphism and blood pressure in Japanese male subjects

Abstract: Inconsistent results have been reported regarding the association of the angiotensin-converting enzyme (ACE) insertion/deletion (I/D) polymorphism and hypertension. Recent studies of population-based samples of three different areas in Japan presented conflicting results regarding this association. We, thus, investigated the relation between the ACE I/D polymorphism and blood pressure (BP), or the frequency of hypertension, respectively, in 706 Japanese male subjects who participated in the health check-up pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The association between ACE Ins/ Del polymorphism and hypertension found in older men in our study was also previously demonstrated in Japanese men (52). The results from these studies suggest that gender, age, and ethnic origin contribute to differences in the association of ACE Ins/Del polymorphism with hypertension and blood pressure variations.…”
Section: Discussionsupporting
confidence: 82%
“…The association between ACE Ins/ Del polymorphism and hypertension found in older men in our study was also previously demonstrated in Japanese men (52). The results from these studies suggest that gender, age, and ethnic origin contribute to differences in the association of ACE Ins/Del polymorphism with hypertension and blood pressure variations.…”
Section: Discussionsupporting
confidence: 82%
“…smokers versus nonsmokers (24), and male versus female (8,9,14,18,19,25) have been reported; failure to account for these interactions may explain, in part, the conflicting findings.…”
mentioning
confidence: 99%
“…Although some researchers have found an association between hypertension and the ACE D allele in men but not in women (Higaki et al 2000;Kimura et al 1997;O'Donnell et al 1998;Todoroki et al 2003), such a gender-specific association has not been verified in other studies (Tamaki et al 2002;Matsubara et al 2002;Sugiyama et al 1999). Although Myerson et al (1999) reported no gender effect on the association between the ACE genotype and endurance performance, a detailed examination of gender specificity between ACE I/D and physical performance has not yet been performed.…”
Section: Introductionmentioning
confidence: 80%
“…As with the association between ACE I/D and hypertension, we hypothesized that there exists a gender difference between ACE I/D polymorphism and race distance (Higaki et al 2000;Kimura et al 1997;O'Donnell et al 1998;Todoroki et al 2003), and used multinomial regression analysis for race distance by using ACE genotype and gender as independent variables.…”
Section: Introductionmentioning
confidence: 99%